Sikap tentang aborsi pada siswi kelas XI - Farikhah Nur Laila; Yani Widyastuti; Hesty Widyasih (Jurnal Kesehatan Ibu dan Anak, 2015)
Teenage pregnancy is closely related to unwanted pregnancy. The number of teenage pregnancies has increased based on SDKI2007 to 2012. The aspects that need to be highlighted as a result of the end of unwanted pregnancy one is abortion. In Indonesia theabortion cases increase in 2012 with eight people died. From the data of SKRRI in 2007 on Indonesian teenagers and theirpermissive attitude toward abortion, the highest percentage is those women who are still in school (37.5%). This study is aimed todetermine the description on abortion of the students in class XI at SMAN 11 Yogyakarta in 2015. This study is descriptive methodwith cross-sectional design. There are 156 respondents. The data measured are attitudes about abortion using questionnaire. Thedata analysis is performed using univariate. The result shows as many as 82 students (52.6%) of grade XI have positive attitudeabout abortion. Meanwhile, those having negative attitude are 74 respondents (47.4%). Those having positive attitude are the onesmajoring in science, residing in urban areas, obtaining dominant sources of reproductive health information fromparents and havingat least 3 sources of reproductive health information. Themajority students of class XI have positive attitude about abortion.